"Revealing the extraordinary in the ordinary": rhythmanalysis and employment related geographical mobilities of Newfoundland and Labrador home care workers. Issue 2 (4th May 2021) - Fitzpatrick, Kathleen
ABSTRACT: This paper uses an intersectional rhythmanalysis approach to examine the predominantly female, working-class home care workers' employment-related geographical mobility (E-RGM) (their mobility to, from and within work) in two very different contexts: workers living and working in St. John's, Newfoundland and Labrador, a small city on Canada's east coast, and workers living in Southwest Newfoundland, a rural region of the same province and working in a different province. This paper seeks to: 1) document the rhythms associated with these two patterns of E-RGM; 2) explore the eurhythmias (rhythms in harmony) and arrhythmias (rhythms in disharmony) associated with these and their consequences for the workers involved; and 3) investigate how rhythms relate to gender and class. This paper adds to the research on intersectional rhythmanalysis by comparing the rhythms of workers in the same position but engaged in two very different forms of E-RGM and the arrhythmias and "fragile synchronicities" associated with each. Common rhythms influencing and influenced by E-RGMs include those related to transportation schedules, weather, care cycles, worker's stage of life, client's natural rhythms, family rhythms, and work schedules. Arrhythmias occur during care cycles, severe weather, and irregular work schedules and are reflected in precarious employment. Eurhythmias occur when home care work cycles, client's natural rhythms, and family rhythms are in sync, but these are often in "fragile synchronicity." Gender relations and class relations (re)constitute the rhythms of these workers' everyday lives.